(untitled) (Indian Journal of Pure & Applied Physics (IJPAP), 2024)
In the current study, we have developed a theoretical model of a plasma cylinder having radius 2 cm and considering electrons, light potassium ( ) positive and heavy ( ) positive ion species inside it. Through one end of the cylinder, an ion beam with energy of 10 eV and a radius of approximately 2cm is injected parallel to the static magnetic field. Fluid theory is applied to perform the numerical calculations of the frequency and the growth rate for both the positive unstable ion modes. The comparative analysis is performed between growth rate and the concentration of positive ions, and we found that it scales as the cube root of the ion beam density and rises as the relative concentration of positive ions increases. However, in comparison to the heavy positive ion mode, our growth rate increases more quickly for the light positive ion mode. Moreover, the unstable wave frequency and the corresponding wave number for both light and heavy positive ion modes are obtained by the point of intersection method. The results show that the unstable wave frequency increases with one-half power of ion beam energy for both the cases but the increase in unstable frequency is much greater for the light positive ion mode as compared to the heavy positive ion mode. As we know that the earth’s ionosphere contains multi positive ion species and the concentration of these species alters the properties of the plasma present in ionosphere, therefore, the observations presented in this study may be helpful in understanding the factors affecting plasma.